A Study of Viscous Dampers for Enhanced Seismic Performance in Reinforced Concrete Multi-Storey Building - Ullah, Fawad; Hamza, Muhammad Ameer; Butt, Jamal; Usama, Muhammad; Ullah, Ubaid (Iraqi Journal of Civil Engineering, 2025)
This study investigates the seismic performance of a nine-storey reinforced concrete building located in Seismic Zone 3, focusing on the effectiveness of viscous dampers in enhancing structural resilience. With increasing seismic risks, the integration of damping systems has become critical for mitigating vibrations and improving building safety. The research evaluates four configurations: a fixed-base building with no dampers, buildings with corner dampers featuring uniform and varying force capacities, and a building with middle dampers. The Equivalent Static Load (ESL) and Response Spectrum study (RSA) methods are used in the ETABS 2021 research to look at important factors such the natural period, storey stiffness, storey drift, storey displacement, and overturning moments.   These steps are based on the UBC 97 criteria.    The results show that viscous dampers do assist structures stay standing during earthquakes.    Buildings with corner dampers that could handle different amounts of stress had a natural period that was 37.5% shorter. This means that they were stiffer and could respond to seismic shocks faster. The storey's stiffness went down by 16.7%, and the periods of overturning went down by 5.7%.   This shows that the dampers did a great job of getting rid of energy.    Also, the maximum storey displacement and drift were 41.6% and 48.14% lower than in the fixed-base model, respectively.    These figures show how important it is to put dampers in the right places, especially at corners where the force capacity changes, to make buildings more resistant to earthquakes. The study's conclusion is that viscous dampers make multi-story structures in moderate seismic zones much safer by making them less likely to break and improving how effectively they perform. This study gives engineers and designers important information that makes them desire to use current dampening technologies in tall buildings to make them safer during earthquakes.